Producing a Rationale for Dowry? Gender in the Negotiation of Exchange at Marriage in Kerala, South India - Praveena Kodoth (Asia Research Centre (ARC), London School of Economics & Political Science, 2006)
Apparently against the grain of evidence of the expanding dimensions of dowry in India, the matrilineal castes in northern Kerala (India) rejected dowry transactions and considered them demeaning. They resorted to dowry only in circumstances considered exceptional. Foregrounding the negative discourse on dowry, this paper explores the ways in which gender enters into the negotiation of exchange during match making, producing a residual category of women for whom demands for dowry were entertained. These women were marked by a combination of poor social, economic and normative gender attributes, which restricted their access to patriarchal norms of femininity and relegated them to the margins of the marriage market. Their experience exposed the underbelly of ‘respectability’ in the region. The pressure to bring women under conjugal patronage compromised reciprocity in match making and generated a ‘practical’ rationale for dowry. Our analysis suggests that if it is to address dowry seriously, social policy in India must combat the centrality accorded to conjugality in the social construction of women’s interests and identity.